Developing Web-Based Point of Sales Application with SHA-512 Encryption on DBMS for Indonesian MSME’s Culinary Industry - Regant Fernando; Jansen Wiratama (Universitas Bina Darma, 2023)
Efficiency and effectiveness are crucial in the food & beverage industry. Conventional methods employed by companies often lead to discrepancies between actual stock and the stock available for sale, resulting in significant losses. To address this issue, a point-of-sales-based system has been implemented, enabling companies to monitor transaction activities seamlessly. The research utilized the RAD (Rapid Application Development) method to develop a concise and fast software application. Furthermore, hashing and encryption methods have been incorporated to enhance database security, utilizing the SHA-512 algorithm for hashing and data encryption. This research has yielded a point-of-sales website-based application that supports various business processes. The website has been tailored to meet the specific requirements outlined by the company owner. The UAT test results have demonstrated that the application encompasses